Proceedings of the 25th International Conference on World Wide Web 2016
DOI: 10.1145/2872427.2883063
|View full text |Cite
|
Sign up to set email alerts
|

Social Networks Under Stress

Abstract: Social network research has begun to take advantage of finegrained communications regarding coordination, decisionmaking, and knowledge sharing. These studies, however, have not generally analyzed how external events are associated with a social network's structure and communicative properties. Here, we study how external events are associated with a network's change in structure and communications. Analyzing a complete dataset of millions of instant messages among the decision-makers in a large hedge fund and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(25 citation statements)
references
References 55 publications
(31 reference statements)
1
23
0
Order By: Relevance
“…Moreover, very little research in the social sciences has examined changes in networks in response to large-scale exogenous shocks (Romero, Uzzi, and Kleinberg 2016). While research has found an increase in network cohesion and network shrinkage in response to natural disasters (Forgette et al 2009;Phan and Airoldi 2015), as well as a tendency to "turtle up" or an intensification of strong-tie interactions and clustering following price shocks (Romero et al 2016), further research is needed to understand how networks have changed during COVID-19. We utilize longitudinal social network data collected pre-COVID (June 2019) and compare them with data collected in June of 2020 to examine changes in social networks following a period of intense social isolation.…”
Section: Original Articlementioning
confidence: 99%
“…Moreover, very little research in the social sciences has examined changes in networks in response to large-scale exogenous shocks (Romero, Uzzi, and Kleinberg 2016). While research has found an increase in network cohesion and network shrinkage in response to natural disasters (Forgette et al 2009;Phan and Airoldi 2015), as well as a tendency to "turtle up" or an intensification of strong-tie interactions and clustering following price shocks (Romero et al 2016), further research is needed to understand how networks have changed during COVID-19. We utilize longitudinal social network data collected pre-COVID (June 2019) and compare them with data collected in June of 2020 to examine changes in social networks following a period of intense social isolation.…”
Section: Original Articlementioning
confidence: 99%
“…Text mining provides technical support for further investigation of contents beyond merely structural or temporal properties of cascades. A number of studies have adopted the word-emotion association lexicon to make automatic evaluation of sentiments and emotions embedded in texts [8,11,41,48]. In addition, topic modeling is another widely used method to quantify the underlying topic concerns that characterize a set of documents [6,21,35,45,48,50].…”
Section: Text Miningmentioning
confidence: 99%
“…Moreover, we are particularly interested in the network response to external stimuli that lead to increased collective attention in the controversial topic -an issue that only very recently has seen some attention in the literature (Romero, Uzzi, and Kleinberg 2016). 3 Dataset…”
Section: Related Workmentioning
confidence: 99%